The Name Jar Project: Supporting Preservice Teachers in Working with English Language Learners - Kapoyannis, Theodora (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2021)
Classrooms are becoming more linguistically and culturally diverse and many educators are feeling unprepared to meet the varied needs of English language learners (ELLs). Through a larger design-based research doctoral study, I collaborated with 11 preservice teachers and 28 ELLs in Grades 2 and 3 to design and implement a literacy intervention that focused on cultivating literacy engagement to foster English language development. This paper documents the positive impact the implementation of the literacy intervention, also known as the Name Jar Project, had on supporting the preservice teachers’ emerging practice. Analysis of focus group data, preservice teachers’ written reflections, and field notes revealed that (a) the preservice teachers, through their informal learning experiences, were able to empathize with the ELLs’ strengths and challenges of learning English; (b) the service learning model provided a safe learning environment for preservice teachers to gain practical experience working with ELLs; and (c) through the research design, preservice teachers connected practice and theory to inform their future teaching experiences.